Influence of marital and family relations on demographic processes in Ukraine - N.M. Ohareva; D.O. Hrytsyshen (Економіка, управління та адміністрування)
The article is an analytical study of the development of marital and family relations from the time of Ukraineʼs independence to the present day and their impact on the countryʼs demographic processes. It has been clarified how family values affect the preservation of marriage and harmonizing relations between partners. The issue of the influence of psychological readiness for marriage, the formation of young peopleʼs knowledge about the essence of married life, stable and comfortable relationships in the future is also highlighted. The problems of family conflicts, distribution of roles between partners, value and moral norms in family relations are considered. The dynamics of registered marriages and divorces since the independence of Ukraine and their influence on the birth rate have been analyzed. Modern scientists single out the main problems of Ukrainian families: from a social point of view, it is a high level of population poverty and low monetary income; improper living conditions and unorganized life; from a demographic point of view – this is a decrease in the birth rate and an increase in the death rate of the population; lack of natural growth; the aging of the population and the reduction of life expectancy of both sexes; deterioration of the nationʼs health; the intensity of migration processes, the increase of the «load» on its working part; from a psychological point of view – these are negative forms of experiencing emotional states: mood, affect, stress, distress, frustration; psychological unreadiness for marriage; lack of knowledge and violated value orientations; lack of common interests; loss of feeling of love; incompatibility of characters; unwillingness to improve and lack of concern for the partner; frivolous attitude to family responsibilities; differences in religious views; sexual dissatisfaction and infidelity; alcohol, drug or gaming addiction. Therefore, in Ukraine, the problem of the countryʼs demographic security is becoming extremely urgent. To improve the demographic situation in the country and reduce the number of divorces, a comprehensive approach is needed: attractive changes in all spheres of social life should be aimed at systematically solving demographic problems. This requires certain developments and implementation, namely: a long-term national strategy to reduce divorce and overcome population depopulation; to clearly forecast a complex system of measures as an economic, social, legal, educational-cultural, spiritual and information-propaganda lever.